Generation and application of DNA aptamers against HspX for accurate diagnosis of tuberculous meningitis - Dhiman, Abhijeet; Haldar, Sagarika; Mishra, Subodh Kumar; Sharma, Neera; Bansal, Anjali; Ahmad, Yusra; Kumar, Amit; Sharma, Tarun Kumar; Tyagi, Jaya Sivaswami (Tuberculosis (Edinburgh, Scotland), 2018)
Tuberculous meningitis (TBM) is the most severe manifestation of tuberculosis and its diagnosis remains a challenge even today due to the lack of an adequate test. HspX antigen of Mycobacterium tuberculosis was previously established as a reliable diagnostic biomarker for TBM in an ELISA test format using anti-HspX polyclonal antibodies. Towards overcoming the limitations of batch-to-batch variation and challenges of scalability in antibody generation, we utilized Systematic Evolution of Ligands by EXponential enrichment (SELEX) to develop high affinity DNA aptamers against HspX as an alternative diagnostic reagent. Post-SELEX optimization of the best-performing aptamer candidate, H63, established its derivative H63 SL-2 M6 to be superior to its parent. Aptamer H63 SL-2 M6 displayed a specific and high affinity interaction with HspX (Kd ∼9.0 × 10−8 M). In an Aptamer Linked Immobilized Sorbent Assay (ALISA), H63 SL-2 M6 significantly differentiated between cerebrospinal fluid specimens from TBM and non-TBM subjects (n = 87, ***p < 0.0001) with ∼100% sensitivity and ∼91% specificity. Notably, ALISA exhibited comparable performance with previously reported antibody-based ELISA and qPCR. Altogether, our findings establish the utility of HspX aptamer for the reliable diagnosis of TBM and pave the way for developing an aptamer-based point-of-care test for TBM.